2021
DOI: 10.1117/1.oe.60.10.104106
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of coherence scanning interferometry using classical Fourier optics

Abstract: We propose a model for coherence scanning interferometry using familiar Fourier optics methods and the spectrum of plane waves for the case where light source spectral bandwidth limits the fringe contrast as a function of optical path length. The model is straightforward to implement, is computationally efficient, and reveals many of the common error sources related to the optical filtering properties of the imaging system. We quantify the limits of applicability of the model related to the geometrical approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…It has also been shown that for continuous surfaces with modest slopes and for small discontinuities (steps), an approximate elementary Fourier optics (EFO) method provides comparable accuracy to more advanced models [13]. The applicability of EFO modeling is consistent with SFR and ITF prediction for interferometers that use phase analysis to determine the final measured topography [14].…”
mentioning
confidence: 69%
“…It has also been shown that for continuous surfaces with modest slopes and for small discontinuities (steps), an approximate elementary Fourier optics (EFO) method provides comparable accuracy to more advanced models [13]. The applicability of EFO modeling is consistent with SFR and ITF prediction for interferometers that use phase analysis to determine the final measured topography [14].…”
mentioning
confidence: 69%
“…However, if in addition the slope of the phase along the fringe frequency is considered, the 2π-ambiguity can be overcome enabling an unambiguous profile reconstruction. This is the basic idea of the FDA algorithm introduced 30 years ago by de Groot et al 21,22 However, the envelope position results from the slope of the phase with respect to the fringe frequency. According to Figure 1 this slope shows a linear behaviour.…”
Section: Extended Signal Analysis In Coherence Scanning Interferometrymentioning
confidence: 99%
“…The signal modeling requires tools such as rigorous coupled wave analysis (RCWA) to predict the scatterometry signals [247]. RCWA is an established calculation method for scatterometry of grating structures in semiconductor wafer process metrology and has been applied to interference microscopy to better understand the imaging properties of these tools [245,248,249].…”
Section: Interferometric Scatterometrymentioning
confidence: 99%